Helicobacter pylori Infection in Children with Recurrent Abdominal Pain and Positive Biopsy Findings - Yusri Dianne Jurnalis; Yorva Sayoeti; Sari Dewi (The Indonesian Society for Digestive Endoscopy, 2013)
Risk factors for Helicobacter pylori (H. pylori) infection include residence in a developing country, poor socio-economic status, overcrowding family, ethnic and genetic predisposition. The diagnosis and management H. pylori have not been satisfied yet; however, there is a problem of increasing H. pylori antibiotic resistance. We reported a case of 8 year-old girl who suffered from H. pylori infection. The diagnosis was made based on history, clinical findings, and laboratory work-up. Suspicion of H. pylori infection was started when she had recurrent abdominal pain. The result of serologic testing for H. pylori immunoglobulin G (IgG) was positive. Endoscopic biopsy revealed the presence of H. pylori. Patient received regimens for first line eradication of H. pylori, i.e. amoxicillin, clarithromycin and omeprazole for two weeks. Afterward, her condition improved markedly without any further complaint.Keywords: Helicobacter pylori, children, recurrent abdominal pain